2018
DOI: 10.3390/molecules23020388
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Melatonin Mitigates Acid Rain Stress to Tomato Plants through Modulation of Leaf Ultrastructure, Photosynthesis and Antioxidant Potential

Abstract: Acid rain (AR) is a serious global environmental issue causing physio-morphological changes in plants. Melatonin, as an indoleamine molecule, has been known to mediate many physiological processes in plants under different kinds of environmental stress. However, the role of melatonin in acid rain stress tolerance remains inexpressible. This study investigated the possible role of melatonin on different physiological responses involving reactive oxygen species (ROS) metabolism in tomato plants under simulated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 57 publications
7
55
0
Order By: Relevance
“…Abiotic stresses, such as drought, cold, and strong light, elevated temperatures along with heavy metal poisoning, can result in the distortion of the electron transport chain (ETC), leading to photo‐oxidation and sequential reduction in the photosynthetic efficiency in plants . It is also noteworthy that these stressful environments induce ultrastructural changes, particularly in leaf mitochondria and chloroplasts; this leads to excessive production of ROS . The photosynthetic effectiveness is determined by the chlorophyll content as elevated ROS causing a drop in the chlorophyll content in plants .…”
Section: Mel Boosts Photosynthesis Pigmentation and Product Yield Imentioning
confidence: 99%
See 1 more Smart Citation
“…Abiotic stresses, such as drought, cold, and strong light, elevated temperatures along with heavy metal poisoning, can result in the distortion of the electron transport chain (ETC), leading to photo‐oxidation and sequential reduction in the photosynthetic efficiency in plants . It is also noteworthy that these stressful environments induce ultrastructural changes, particularly in leaf mitochondria and chloroplasts; this leads to excessive production of ROS . The photosynthetic effectiveness is determined by the chlorophyll content as elevated ROS causing a drop in the chlorophyll content in plants .…”
Section: Mel Boosts Photosynthesis Pigmentation and Product Yield Imentioning
confidence: 99%
“…Estimating chlorophyll fluorescence is a rapid, persuasive, and reliable method for determining the photosynthesis processes in plants . Remarkably, the primary photosystem (PSII) of the photosynthetic machinery ( F o and F o /F m value) is essential in the transformation of energy and thereby serves as an excellent marker of stress in plants . Clearly, it becomes imperative to alter the effectiveness of this profit‐yielding mechanism for improved growth and development of plants under capricious environments.…”
Section: Mel Boosts Photosynthesis Pigmentation and Product Yield Imentioning
confidence: 99%
“…It was hypothesized that melatonin act as the first line defense to protect plants against biotic and abiotic stress, and the mechanisms of melatonin-mediated stress tolerance are involved in arranging biosynthesis of antioxidants, activating related enzyme activities and scavenging ROS directly when plants are exposed to harsh environments such as extreme temperature, cold, drought, salt and oxidative stress [ 26 , 27 , 28 ]. Moreover, our previous studies exposed that exogenous melatonin improved the photosynthesis systems and ROS-scavenging antioxidant activities which lead to enhanced the SAR-stress tolerance in tomato plants [ 29 ]. Currently, it has been demonstrated that the presence of melatonin in different parts of plants such as the roots, stems, leaves, flowers, fruits, and seeds [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1, the content of TPC, TFC and TFAC in melatonin application group significantly increased than control. Additionally, Debnath et al found melatonin caused increase of phenolic compounds content to scavenge the ROS induced by acid rain [8].…”
Section: Discussionmentioning
confidence: 99%